Analysis of Contact System for Organic and Inorganic Pesticide Residues on Cayenne Pepper (Capsicum annuum) - A. Rumaisha Ramli; Rita Hayati; Muhammad Sayuthi (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
The aim of this study is to find out Contact System for Organic and Inorganic Pesticide Residues on Cayenne Pepper. This study used the Factorial Completely Randomized Design (CRD) method with 2 treatment factors. The results of the research on cayenne pepper resulted from the interaction of 0.5 ml / l water (K1) of inorganic pesticides with various levels of organic pesticides having a capsaicin level range between 0.078% to 0.080%. Where the lowest percentage of capsaicin levels was obtained at the interaction with Organic Pesticides at the level of 0 ml / l water (P0) which was significantly different from the interaction of Organic Pesticides at the level of 200 ml / l water (P1). The percentage of capsaicin levels is better obtained at the interaction with organic pesticides at the level of 200 ml / l water (P1) which is significantly different from the interaction of Organic Pesticides at the level of 0 ml / l water (P1) and at the level of 600 ml / l water (P3).